Synthesis of C-5a-substituted derivatives of 4-epi-isofagomine: notable β-galactosidase inhibitors and activity promotors of GM1-gangliosidosis related human lysosomal β-galactosidase mutant R201C. (24th June 2016) - Thonhofer, Martin; Weber, Patrick; Gonzalez Santana, Andres; Tysoe, Christina; Fischer, Roland; Pabst, Bettina M.; Paschke, Eduard; Schalli, Michael; Stütz, Arnold E.; Tschernutter, Marion; Windischhofer, Werner; Withers, Stephen G.
Graphical Abstract: Highlights: The first synthesis of (5a S )-chain extended 4-epi-isofagomines. New compounds are powerful β-galactosidase inhibitors. Residual human β-galactosidase activity of mutant R201C is enhanced up to 10-fold (at 2.5 µM). Abstract: From an easily available partially protected analog of 1-deoxy-L- gulo -nojirimycin, by chain-branching at C-4 and suitable modification, lipophilic analogs of the powerful β-D-galactosidase inhibitor 4-epi-isofagomine have been prepared. New compounds exhibit considerably improved inhibitory activities when compared with the unsubstituted parent compound and may serve as leads toward new pharmacological chaperones for GM1 -gangliosidosis and Morquio B disease.